Mutagenesis analysis of T380R mutation in the envelope protein of yellow fever virus - Huang, Yan-Jang S.; Nuckols, John T.; Horne, Kate M.; Vanlandingham, Dana L.; Lobigs, Mario; Higgs, Stephen (My University, 2014)
Background: The RGD motif in the mosquito-borne flaviviruses envelope protein domain III (EDIII) FG loop was shown to bind negatively charged cellular molecules and mediate virus entry in mammals. However, its importance in virus entry in the mosquito has not yet been defined. The sequences of RGD motifs are conserved in JEV-serocomplex members primarily transmitted by Culex mosquitoes but absent from members of the DENV serocomplex, which utilize Aedes mosquitoes as vectors. Interestingly, the RGD sequence is present in the attenuated 17D strain of yellow fever virus as a result of the T380R mutation in the EDIII of Asibi strain following extensive in vitro passage in mice and chicken embryos and was found to contribute to the more rapid clearance in mice challenged with 17D. However, viral infectivity and dissemination in mosquitoes had not been evaluated for this mutant. Findings: The study utilized the reverse genetics system of YFV and Ae. aegypti RexD WE mosquitoes to assess the impact of a T380R mutation in YFV Asibi and 17D/Asibi M-E chimera. The T380R mutation led to higher infection rates but similar dissemination rates when introduced into the YFV Asibi strain and 17D/Asibi M-E chimera. Conclusions: While the increase of the positive charge in EDIII may reduce the virulence of YFV in mice, this mutation favored the establishment of the viral infection in Ae. aegypti. However, such gain in viral infectivity did not increase dissemination in infected mosquitoes.
Keywords: Yellow fever virus; 17D vaccine; Aedes aegypti